Association between age and achilles cross-sectional area in NCAA division one collegiate female gymnast - Bates, C. J.; Hinkle, L. J; Schaugaard, B.; Hartog, P.; Davidson, G.; Johnson, A. W. (International Journal of Exercise Science Conference Proceedings, 2025)
Monitoring changes in Achilles cross-sectional area (CSA) or thickness may provide clinicians with insights into exercise-induced adaptations and the mechanisms of Achilles tendon injury. It has been reported that an increase in thickness of 20% or more along the course of the Achilles tendon from the proximal calcaneus may be a clinical sign of structural pathology. Evaluating the relationship between an athlete`s age and Achilles tendon thickness may offer a valuable metric for understanding tendon health.